The importance of intramedullary hip nail positioning during implantation for stable pertrochanteric fractures: biomechanical analysis - Bartoska, Radek; Baca, Vaclav; Horak, Zdenek; Hrubina, Maros; Skala-Rosenbaum, Jiri; Marvan, Jiri; Kachlik, David; Dzupa, Valer (Surgical and radiologic anatomy, 2016)
PURPOSE: Proximal femoral fractures are among the most commonly sustained fractures. The current treatment of stable proximal femoral fractures located in trochanteric region primarily involves the use of two systems: extramedullary dynamic hip screws and intramedullary hip nails. Given that these fractures are mainly found in the elderly population, the necessity of a repeat, due to failure of the first, may jeopardize the patient's life. Decisive factors contributing to the healing of a fracture (or the failure thereof) include fracture pattern, technical implementation of the operation (i.e., position of the implant), implant's properties and its changes in relation to the surrounding bone tissue during loading. Each screw insertion variant results in damage to various load-bearing bone structures, which can be expected to influence healing quality and stability of newly formed bone. METHOD: With the aid of a numerical model and finite element methods, the authors analyzed several different positions of IMHN/PFH-nails in the proximal femur, with the objective of determining positions with an increased risk of failure. RESULTS AND CONCLUSION: In model situations, it has been shown that in stable fractures results do not depend on absolutely precise positioning and small deflections in the nails and neck screws positions do not significantly increase the risk of failure for the entire fixation. Damage to load-bearing structures relative to various implant placements does not impact the resultant overall fixation stability. Therefore, it is not necessary to re-introduce implants in the ideal position, which can lead to reduced patient radiation doses during surgery.
Keywords: Stable pertrochanteric fracture; Treatment Failure; intramedulární fixace fraktury; neúspěšná terapie; Femur; zatížení muskuloskeletálního systému; Risk Factors; Finite element method analyses; analýza metodou konečných prvků; Intramedullary hip nail; kostní hřeby; Fracture Fixation, Intramedullary; teoretické modely; Complications; Biomechanical Phenomena; Aged; senioři; Hip Fractures; biomechanika; Models, Theoretical; lidé; Finite Element Analysis; Humans; rizikové faktory; Bone Nails; femur; Weight-Bearing; Bone fixation; fraktury kyčle